A Note on Method of Propagation of Costus speciosus (Koen.) Sm. - Verma, V. P. S.; Sharma, B. K. (Indian Forester, 1978)
The common method of propagation of Costus speciosus (Koen.) Sm. Is by planting rhizome cuttings. Since rhizomes of this species are used for extraction of diosgenin, their use as planting material means loss Of diosgenin. An alternative method of propagating the species by planting saplings raised from sprouted node buds, is reported.